2021
DOI: 10.31129/lumat.9.1.1637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resource-based instructions on pre-service biology teachers’ motivation toward learning biology

Abstract: Linking motivation and learning is central to understanding students’ motivation toward learning and learning itself as complex cognitive phenomena. Some studies focused on students’ motivation toward learning biology in general; however, the shortage of studies on the effect of animation-based instruction and small-group laboratory activities as Resource-based Instructions (RBIs) on pre-service biology teachers was realized. The present study aimed to determine the effect of resource-based Instructions on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 83%
“…Upon intervention, either inquiry-based learning or conventional teaching method influence an increase in attitude change. This was confirmed by Rogayan (2019); Mukagihana et al (2021a), asserting that after learning, students improve their attitude towards biology regardless of the teaching techniques they went through. Nevertheless, statistical results with a one-way variance analysis showed a significant difference in attitude change between the two groups in favor of the experimental group taught with inquiry-based learning at a .05 significance level.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The need for motivation in learning biology was explored by Mukagihana et al. (2021) and found that there was no statistically significant difference in the motivation of learning the biology of pre-service teachers before and after learning with traditional instruction at a public university while this difference was found statistically significant via animation instruction.…”
Section: Introductionmentioning
confidence: 99%
“…The need for motivation in learning biology was explored by Mukagihana et al (2021) and found that there was no statistically significant difference in the motivation of learning the biology of pre-service teachers before and after learning with traditional instruction at a public university while this difference was found statistically significant via animation instruction. The findings from the study of Sibomana et al (2021) showed that the lack of insufficient instructional materials, science laboratories, and the predominant use of teacher-centered methods decrease students' interest in learning and hence perform poorly.…”
Section: Introductionmentioning
confidence: 99%